Pengaruh Persepsi Harga, Kualitas Produk, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Furnitur - Depi Ratna Sari; Rama Chandra Jaya; Dadan Abdul Aziz Mubarok (IKRAITH-EKONOMIKA, 2025)
This study aims to examine the effect of price perception, product quality, and service quality on consumers’ purchasing decisions at Koenig Furniture. A quantitative method with descriptive and verificative approaches was employed. The population comprised all Koenig Furniture consumers, with a sample of 100 respondents selected using purposive sampling, a type of non-probability sampling. Data analysis was conducted using Multiple Linear Regression, hypothesis testing (t-test and F-test), and the Coefficient of Determination. The results show that individually, price perception, product quality, and service quality have a positive and significant impact on purchasing decisions, with significance values of 0.000 < 0.05 for each variable. This indicates that appropriate pricing, product durability, and responsive service are crucial factors influencing consumer purchase behavior. Collectively, the three variables also exert a significant simultaneous effect on purchasing decisions, with an F-value of 86.465 and a significance of 0.000. The R² value indicates that 72.1% of the variation in purchasing decisions is explained by price perception, product quality, and service quality, while the remaining 27.9% is attributed to other factors outside the scope of this study.